2011
DOI: 10.1093/rheumatology/ker421
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the current disease severity scores in paediatric FMF: is it necessary to develop a new one?

Abstract: The inconsistency of the two scoring systems and lack of correlation between the scoring systems and mutation groups raises concerns about the reliability of these scoring systems in children. There is a need to develop a scoring system in children based on a prospective registry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 20 publications
(51 reference statements)
1
20
0
Order By: Relevance
“…Additionally, Kalkan et al (25) reported that a new disease severity scoring system must be developed for children with FMF to facilitate assessment of daily care performance or individual patient prognosis and guide care. …”
Section: Disease Severity Scorementioning
confidence: 99%
“…Additionally, Kalkan et al (25) reported that a new disease severity scoring system must be developed for children with FMF to facilitate assessment of daily care performance or individual patient prognosis and guide care. …”
Section: Disease Severity Scorementioning
confidence: 99%
“…The particu lar muta tions mentioned by Kalkan et al 2 were found in only 38% of Turkish children with amyloidosis, the proto typical severe manifestation of the disease; the major ity of this cohort carried other mutations usually found in patients with mild disease. 5 In another study of 102 Turkish children, neither er ysipelaslike erythema (ELE) nor pleuri tic chest pain were associated with specific geno types, despite being pheno typic markers of increased disease severity.…”
Section: Papermentioning
confidence: 58%
“…This conclusion should, however, be care fully evaluated in light of some limitations in the methodology of the Kalkan et al 2 …”
mentioning
confidence: 98%
See 1 more Smart Citation
“…However, the performance of the two modifi ed sets did not correlate with each other, giving the impression that a well-performing pediatric score tool needs to be created [ 8 , 29 ]. Therefore, another severity score is currently being established, this time, by an international consortium consisting of experts across the Mediterranean basin, with extensive clinical experience in FMF [ 29 ]. The goal of the project was to develop widely accepted international severity score for children and adult patients with FMF that can be easily applied in research and clinical practice.…”
Section: Severity Scoring Systemsmentioning
confidence: 99%